Меню

УСЛОВИЕ:
Найдите корни уравнения: 5)1/6(х+9)=-1/3х 6)3/4(х+8)=2х+1 / дробь Упростите выражение:

1)6а*(-2b)*(-с) 3)-5/6а*(-4/5b)*3/8 3)-0,5а*(-7b)*(-2с) 4)-4m*0,8с*(-5d) / это дробь * это умножить



РЕШЕНИЕ:

1/6(х+9)=-1/3х

1/6х+9/6=-1/3х

1/6х+1/3х=-9/6

3/6х=-9/6

х=-9/6:3/6

х=-3

 

3/4(х+8)=2х+1

3/4х+6=2х+1

3/4х-2х=1-6

-5/4х=-5

х=-5:(-5/4)

х=4

 

6а*(-2b)*(-с)=-12ab*(-c)=12abc

-5/6а*(-4/5b)*3/8=2/3ab*3/8=1/4ab

 

-0,5а*(-7b)*(-2с)=3,5ab*(-2c)=-7abc

 

-4m*0,8с*(-5d)=-3,2mc*(-5d)=16mcd

 






Похожие примеры: